Trade Reform and Inflation Stabilization - Kumar, Manmohan; Arora, Vivek (Washington, D.C. : International Monetary Fund, 1994)
This paper examines two important issues for a small high-inflation open economy with trade controls where the government implements an exchange-rate based stabilization program: first, the extent to which the degree of openness of the economy influences the probability of success of the program; and second, the conditions under which a trade reform, implemented in conjunction with the stabilization program, will increase the probability that stabilization will be successful. The paper shows that in an economy with high export and import price elasticities, structural reforms to increase openness can be important in determining the success of the program.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet